Workshop Literasi Penulisan Penelitian Tindakan Kelas Bagi Guru di MIN Kota Bogor: Pengabdian - Syarif, Ahmad; Ernawati; Sudjana, Dace (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this community service activity is to provide knowledge on how to apply literacy in writing class action research for teachers at MIN Bogor City and facilitate MIN Bogor City teachers in the form of assistance in writing PTK through systematic activity stages. The method of this community service activity uses several stages: the first is the presentation of material related to the literacy of writing class action research for MIN Kota Bogor teachers and the second is assistance related to the literacy of writing class action research for MIN Kota Bogor teachers. The implementation time of the activity was divided into two sessions at the MIN Kota Bogor Hall. The first session, in the morning from 09.00-12.00, presented material on writing strategies, PTK design, and paraphrasing techniques. The second session, from 13.00-15.00 mentoring in the form of practice writing PTK reports. The results of the activity were followed by all MIN teachers in Bogor City with 93% answering the questionnaire very satisfying and 7% answering satisfied with the service activity.